Successful enhanced recovery program after colorectal surgery in the county hospital setting - Aboulian, Armen; Mat Hassan, Mohd. Zailani; Lin, Matthew; Kumar, Ravin R (2010)
In recent years, some enhanced recovery protocols after colorectal surgery have gained some acceptance as they have shown to improve patient recovery and decreased length of hospital stay.This study was designed to assess the feasibility of such a program in a large county hospital with a diverse patient population.